Perspective: could Ethiopian potatoes contribute to environmental sustainability, the Ethiopian economy, and human health? - Yimam, Mohammed Ahmed; Andreini, Martina; Carnevale, Sara; Muscaritoli, Maurizio (Frontiers in Sustainable Food Systems, 2024)
Environmental data are promptly accruing on the unsustainability of diets from animal origin, such as dairy and meats. Shifting to alternative sources of protein is inevitable given an increase in projected global population and protein demand. Left unchecked, a collision happens between food security and sustainability. Potato could be the strategic food and cash crop to harmonize food security and sustainability worldwide. Recently, extracting proteins from the potato starch industry side stream (potato fruit juice) received attention due to their nutritional (well-balanced amino acid profile), functional (emulsifying, foaming and gelling properties) and less allergenic properties. Potato protein is a side stream resource; extracting it reduces food loss and waste, thereby eliminating pathogenic microorganisms from the environment and mitigating greenhouse gas emissions.Ethiopia is the major potato producer in East Africa. Potato helps the country to increase household income, ensure food security and revenue generation, and produce starch. However, the potato starch industry in the country did not extract the proteins yet, despite the vital role of the proteins and the country's huge cultivation potential. Plus, the global potato protein market is escalating. This information urgently calls to provide innovation prospects on the impact of extracting protein from potatoes produced in Ethiopia. Therefore, this perspective article has two objectives. First, to scan the extent of potato production in Ethiopia linked to environmental sustainability, and economy. Second, to provide prospects on the impact of extracting protein isolate from potatoes produced in Ethiopia for environmental sustainability, Ethiopia's economy and human health.